Aphid Feeding Induces Phytohormonal Cross-Talk without Affecting Silicon Defense against Subsequent Chewing Herbivores - Johnson, Scott N. (Plants (Basel), 2020)
Prior feeding by insect herbivores frequently affects plant quality for herbivores that subsequently feed on the plant. Facilitation occurs when one herbivore improves plant quality for other herbivores, including when the former compromises plant defenses. Silicon (Si) is an important defense in grasses that increases following activation of the jasmonic acid (JA) pathway. Given that aphids often stimulate the salicylic acid (SA) pathway, we hypothesized that this could reduce Si defense because of the well documented antagonistic cross-talk between SA and JA. We tested this in the model grass Brachypodium distachyon with and without Si (+Si and −Si, respectively); half of the plants were exposed to aphids (Rhopalosiphum padi) and half remained aphid-free. Aphid-free and aphid-exposed plants were then fed to chewing herbivores (Helicoverpa armigera). Aphids triggered higher SA concentrations which suppressed JA concentrations but this did not affect foliar Si. Chewing herbivores triggered higher JA concentrations and induced Si uptake, regardless of previous feeding by aphids. Chewer growth rates were not impacted by prior aphid herbivory but were reduced by 75% when feeding on +Si plants. We concluded that aphids caused phytohormonal cross-talk but this was overridden by chewing herbivory that also induced Si uptake.